Finite element analysis of mechanical properties for 2D woven kenaf composite - Rejab, Muhammad Nazri (2013)
Woven composite based on natural fiber increasingly used for many applications in industries because of their advantages such as low cost, low weight, less damage to processing equipment, improved surface finish, good relative mechanical properties and renewable resources, but there are some problems as cost and protracted development period to perform reliability evaluation by experimental with real scale. Predictive modeling technique is used to minimize the need for physical testing, shorten design timescales and provide optimized designs. Mechanical properties of woven fabrics for technical textile depend on a) type of raw materials b) type and count of warp and weft yarns c) yarn density and d) the type of weave structure. The effect of fabric architecture to the mechanical properties is investigated. The optimum fabric structure is crucial due to the combination of difference of yarn size and weave pattern are observed. The research is conducted in the microscopic, mesoscopic and the macroscopic scale. The benefit using the hierarchal method of multi scale modeling is: (1) it encourages a reduced reliance on costly trial and error. (2) Lead-time for the introduction of new technologies is reduced, (3) the multi-scale modeling system lowers the likelihood of conservative or compromised designs that might have resulted from reliance on less-than-perfect material. Woven kenaf composite is modeled using the modeling software to get the properties of the model. Further, the model is analyzed using finite element analysis to predict the mechanical properties of the woven kenaf composite. In addition, the effect of the combination of yarn size and weave pattern of the woven kenaf composite is stated based on the mechanical properties to predict the optimum structure of woven kenaf composite.